Pengaruh Kualitas Produk dan Pelayanan Terhadap Tingkat Penjualan di Kedai Fatimah STQ Sangatta Utara - Hafsah; Arif Rembang Supu; Jamila (CV. ITTC INDONESIA, 2025)
The purpose of this study is to analyze the effect of product quality and service on sales levels at Kedai Fatimah STQ Sangatta Utara. This study uses a quantitative approach with a field research type. In data collection, the author uses questionnaire, observation and documentation methods. With a population of 200 customers. The sample is 67 respondents taken using the Purposive Random Sampling technique. In proving and analyzing this, validity and reliability tests, classical assumption tests, simple linear regression tests and f tests and t tests are used. The results of this study analysis indicate that: 1) Product Quality (X1) has a positive and significant effect on Sales Level (Y) at Kedai Fatimah STQ Sangatta Utara. The partial test results show that the t-count value is 4.908> 1.992 with a significance value of 0.000 <0.05. 2) Service (X2) has a positive and significant effect on Sales Level (Y) at Kedai Fatimah STQ Sangatta Utara. The partial test results show that the t-value is 2.343 > 1.992 with a significance value of 0.022 < 0.05. 3) Simultaneously, Product Quality (X1) and Service (X2) have a positive and significant effect on Sales Level (Y) at Kedai Fatimah STQ Sangatta Utara. The results of the F test are f count 12.562 ≥ F table 3.991 with a significance value of 0.001 < 0.05 and have an influence of 64.9%. While 35.1% is influenced by other factors outside the variables used. The conclusion of this study is that product quality and service have a significant effect on increasing sales levels at Kedai Fatimah. Therefore, it is recommended that all UMKM actors, especially in the culinary field, can improve the quality of products and services to increase income.